2005
DOI: 10.1007/s10800-005-9000-3
|View full text |Cite
|
Sign up to set email alerts
|

Copper electrodeposition in sulphate solutions in the presence of benzotriazole

Abstract: DC and pulse plating of copper in acidic sulphate solutions containing benzotriazole (BTA) has been studied. When BTA is the only additive present, it generally has a stronger effect than the plating mode and significantly enhances deposit morphology and surface brightness over that produced in additive-free solutions. XPS and voltammetry analyses indicate that BTA is present at the surface of the deposit, but not through the entire coating, and does not become depleted within the solution over the course of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 46 publications
6
36
0
2
Order By: Relevance
“…For example, Healy & Pletcher (1998a, 1998b have shown that the studied additives (Cl -, polyethylene glycol, and 4,5-dithiaoctane-l,8-disulfonic acid) adsorbed on the electrode at different deposition potentials and stirring speeds influences in the copper reduction mechanism. Similar results were observed by Bozzini et al (2006) and Tantavichet & Pritzker (2006), who studied the effects of polyethylene glycol and benzotriazole, respectively. Nayana et al (2011) have investigated the influence of additives on the morphology and brightness of nanocrystalline zinc electrodeposited from an acid sulfate bath.…”
Section: The Effects Of Other Deposition Parameters On the Coating Prsupporting
confidence: 87%
“…For example, Healy & Pletcher (1998a, 1998b have shown that the studied additives (Cl -, polyethylene glycol, and 4,5-dithiaoctane-l,8-disulfonic acid) adsorbed on the electrode at different deposition potentials and stirring speeds influences in the copper reduction mechanism. Similar results were observed by Bozzini et al (2006) and Tantavichet & Pritzker (2006), who studied the effects of polyethylene glycol and benzotriazole, respectively. Nayana et al (2011) have investigated the influence of additives on the morphology and brightness of nanocrystalline zinc electrodeposited from an acid sulfate bath.…”
Section: The Effects Of Other Deposition Parameters On the Coating Prsupporting
confidence: 87%
“…On the one hand, this film [Cu(I)-BTA] is a physical barrier screening the metal surface from the corrosive ions present in solution, and on the other hand, it binds copper atoms, preventing anodic dissolution and decreasing the electrical conductivity of the surface layer [7]. The following reactions [7][8][9][10] …”
Section: Resultsmentioning
confidence: 99%
“…Benzotriazole (C 6 H 5 N 3 , BTAH) has been extensively studied as an inhibitor for the corrosion of copper and many of its alloys [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], for dezincification of brass [17,18], and as an additive in the etching [19], electrodeposition [20][21][22], and in the chemical mechanical polishing of copper [23][24][25]. It has also been reported to inhibit the corrosion of iron [26][27][28], cobalt [29], zinc [30], and nickel [28] and to enhance the resistance of tin bronze to oxidation in air up to 500 8C [31].…”
Section: Introductionmentioning
confidence: 99%